Delay-Dependent Stability Analysis of Load Frequency Control for Power System With EV Aggregator - Yuan, Zhe-Li; Xu, Da; Jin, Li; Wang, Hong-Zhang (Frontiers in Energy Research, 2021)
In this paper, the exponential stability of load frequency control (LFC) for time-delay power system with electric vehicles (EV) aggregator is studied based on Lyapunov theory and linear matrix inequality. Through mechanism analysis, the LFC of power system with EV aggregator based on PID controller is modeled. By constructing time-delay interval information correlation functional and estimating its derivative usingWirtinger inequality and extended reciprocally convex matrix inequality, a new stability analysis criterion is proposed. Finally, the proposed method is used to discuss the influence of the allowable upper-bound delays on EV aggregator gains and PID controller gains for LFC of power system with EV aggregator participation in frequency regulation, and the effectiveness of the proposed method is verified.